2022
DOI: 10.1103/physrevd.105.023520
|View full text |Cite
|
Sign up to set email alerts
|

Dark Energy Survey Year 3 results: Cosmological constraints from galaxy clustering and weak lensing

Abstract: We present cosmological results from a combined analysis of galaxy clustering and weak gravitational lensing, using 1321 deg 2 of griz imaging data from the first year of the Dark Energy Survey (DES Y1). We combine three two-point functions: (i) the cosmic shear correlation function of 26 million source galaxies in four redshift bins, (ii) the galaxy angular autocorrelation function of 650,000 luminous red galaxies in five redshift bins, and (iii) the galaxy-shear cross-correlation of luminous red galaxy posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
522
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 663 publications
(545 citation statements)
references
References 273 publications
21
522
1
1
Order By: Relevance
“…The Dark Energy Survey (DES) Collaboration demonstrates this idea by using three statistical measurements of galaxies to pin down values for the dark matter density, the cosmic expansion rate, and other parameters in cosmology. The collaboration has now released three years' worth of data, which covers an area of sky three times larger than their previous release [1]. The new analysis supports the standard cosmological model, with the measurements having unprecedented precision.…”
mentioning
confidence: 89%
“…The Dark Energy Survey (DES) Collaboration demonstrates this idea by using three statistical measurements of galaxies to pin down values for the dark matter density, the cosmic expansion rate, and other parameters in cosmology. The collaboration has now released three years' worth of data, which covers an area of sky three times larger than their previous release [1]. The new analysis supports the standard cosmological model, with the measurements having unprecedented precision.…”
mentioning
confidence: 89%
“…Future CMB measurements will have superb precision, and they could discriminate between neutrino interactions and uniformly enhanced lensing [55,57]. Furthermore, current surveys are rapidly improving our precision of the matter power spectrum [10,80], to the extent that they could start being sensitive to effects induced by neutrino self-interactions [27]. The light new scalar responsible for the long-range interaction could also give rise to observable departures from standard cosmology [36][37][38][39][40][41].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The standard cosmological model, remarkably simple but with profound implications, remains strikingly successful in many diverse environments [1][2][3][4][5][6][7][8][9][10][11]. The precision is such, that self-consistency tests are feasible and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…This was soon confirmed by the WMAP CMB observations (Bennett et al 2003;Spergel et al 2003), which showed that the dark energy comprises ∼ 70% of the mass-energy budget of the flat universe, assuming a cosmological constant with equation of state w = −1. Measurements of the present-day dark energy equation of state parameter, assuming standard general relativity (GR), are w = −1.020 ± 0.027 (Alam et al 2021) and w = −1.031 +0.030 −0.027 (Abbott et al 2022). Since the ΛCDM standard model of cosmology was established, the past 20 years have seen an explosive growth of cosmological observations that have continued to support the ΛCDM model with increasingly tight parameter constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Since the ΛCDM standard model of cosmology was established, the past 20 years have seen an explosive growth of cosmological observations that have continued to support the ΛCDM model with increasingly tight parameter constraints. These recent measurement constraints on ΛCDM come from many types of observations, including the CMB (e.g., Hinshaw et al 2013;Planck Collaboration et al 2020a), Type Ia supernovae (SNe Ia; e.g., Scolnic et al 2018), baryon acoustic oscillations (BAO) in the galaxy distribution (e.g., Alam et al 2021;Eisenstein et al 2005), and weak gravitational lensing (Abbott et al 2022;Tröster et al 2021;Heymans et al 2021). Indeed, ΛCDM has survived so many observational tests that is difficult to believe that it can be very far off of reality.…”
Section: Introductionmentioning
confidence: 99%